SARS-CoV-2 RT-PCR assessment in asymptomatic versus symptomatic patients from a tertiary care center with recovery monitoring: A study from Kathmandu, Nepal - Risal, Gaurab; Kadel, Unnati; Pudasaini, Deepa; Adhikari, Saugat; Khadka, Dipendra (Journal of Biomedical Sciences, 2025)
Background: The SARS-CoV-2 infection led to a global health crisis with both symptomatic and asymptomatic cases emerging. This study aimed to study the prevalence of SARS-CoV-2 among both symptomatic and asymptomatic patients visiting a tertiary care hospital in Nepal and to assess the viral load variations in COVID-19 positive cases throughout the recovery period. Material and methods: A cross-sectional study was conducted on symptomatic and asymptomatic patients visiting Shahid Gangalal National Heart Centre, Kathmandu, Nepal, over a five-month study period from December 2021 to March 2022. The real-time (RT) PCR was performed to confirm the presence of SARS-CoV-2, and the reporting was done in terms of the cycle threshold (Ct) value. Results: A total of 3738 samples were tested for SARS-CoV-2 during the study. Among 526(14.1%) cases that tested positive, 423(80.4%) were symptomatic and 103(19.6%) were asymptomatic. The common symptoms observed in the COVID-19 patients in our study were cough and fever. Additionally, by tracking the PCR reports of available patients concerning Ct value, we found that 81.5% of patients recovered by the third week of infection, with individuals aged 60 years or older taking the longest to recover. Conclusion: The findings highlight the prevalence of asymptomatic cases that were widespread during the pandemic. It also implies that the use of reliable diagnostic techniques like RT-PCR with its specific Ct value is important in managing and controlling pandemics like COVID-19.